2023
DOI: 10.1111/mec.17252
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clock‐ and temperature‐associated genes contribute to overall genomic differentiation along elevation in lichenized fungi

Henrique F. Valim,
Francesco Dal Grande,
Edgar L. Y. Wong
et al.

Abstract: Circadian regulation is linked to local environmental adaptation, and many species with broad climatic niches display variation in circadian genes. Here, we hypothesize that lichenizing fungi occupying different climate zones tune their metabolism to local environmental conditions with the help of their circadian systems. We study two species of the genus Umbilicaria occupying similar climatic niches (Mediterranean and the cold temperate) in different continents. Using homology to Neurospora crassa genes, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…This supports the notion that winter temperature shapes mangrove distributions and assemblage composition in China ( Wu et al., 2018 ). Local temperature has been consistently identified as significant drivers of varying selective pressures in many organisms, such as grey mangrove ( Friis et al., 2024 ), lichen-forming fungi ( Valim et al., 2023 ), and mountain pine ( Méndez-Cea et al., 2023 ). In this study, the Fuding and Shenzhen populations showed a higher proportion of fixation in temperature-associated SNPs ( Figure 5C ) compared with genome-wide SNPs ( Figure 1C ), implying that natural selection has facilitated the rapid evolution of genes related to local adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the notion that winter temperature shapes mangrove distributions and assemblage composition in China ( Wu et al., 2018 ). Local temperature has been consistently identified as significant drivers of varying selective pressures in many organisms, such as grey mangrove ( Friis et al., 2024 ), lichen-forming fungi ( Valim et al., 2023 ), and mountain pine ( Méndez-Cea et al., 2023 ). In this study, the Fuding and Shenzhen populations showed a higher proportion of fixation in temperature-associated SNPs ( Figure 5C ) compared with genome-wide SNPs ( Figure 1C ), implying that natural selection has facilitated the rapid evolution of genes related to local adaptation.…”
Section: Discussionmentioning
confidence: 99%